2019
DOI: 10.1038/s41598-018-38172-4
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity pattern and chemical deception in a social parasite of ants

Abstract: In natural ecosystems, relationships between organisms are often characterised by high levels of complexity, where vulnerabilities in multi-trophic systems are difficult to identify, yet variation in specific community modules can be traceable. Within the complex community interactions, we can shed new light on dynamics by which co-evolutionary outcomes can inform science-led conservation. Here we assessed host-ant use in six populations of the butterfly Phengaris (=Maculinea) rebeli, an obligate social parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Ovipositing female Maculinea butterflies do, however, select the buds of their food plants that are in particular growth-forms or phenological stages [31,93,99], and these may occur in microhabitats that may be associated with particular Myrmica species [31]. Ideally, therefore, the encounter filter should be the Myrmica community found around food plants on which eggs have been laid [42], although this effect is likely to be small, especially in comparison with difference in Myrmica communities between areas with and without food plants [89,100,101]. On the other hand, females may avoid plants on which others have laid eggs [102], which will lead to a more even distribution of eggs (and larvae) relative to Myrmica nests [94,97].…”
Section: (B) the Encounter Filtermentioning
confidence: 99%
“…Ovipositing female Maculinea butterflies do, however, select the buds of their food plants that are in particular growth-forms or phenological stages [31,93,99], and these may occur in microhabitats that may be associated with particular Myrmica species [31]. Ideally, therefore, the encounter filter should be the Myrmica community found around food plants on which eggs have been laid [42], although this effect is likely to be small, especially in comparison with difference in Myrmica communities between areas with and without food plants [89,100,101]. On the other hand, females may avoid plants on which others have laid eggs [102], which will lead to a more even distribution of eggs (and larvae) relative to Myrmica nests [94,97].…”
Section: (B) the Encounter Filtermentioning
confidence: 99%
“…Similar strategies were also revealed in non-hymenopteran parasites of Hymenoptera hosts. For example, Casacci et al [28] found that parasitic caterpillars (Phengaris (=Maculinea) rebeli (Hirschke, 1904)) show local variations in host (Myrmica ants) specificity, which are consistent with CHC similarities between hosts and parasites at different sites. Local adaptations in chemical deceptive signals were also detected in the parasitic beetle Meloe franciscanus Van Dyke, 1928 attacking two allopatric populations of Habropoda solitary bees [27].…”
Section: Discussionmentioning
confidence: 87%
“…Because of its low host specialization, however, P. grandior would not be able to chemically match all available hosts at a given location, given that CHC profiles tend to be species-specific in insects [7,13]. In particular, we might document local adaptation to one of the host species as shown in other insect brood parasites, including socially parasitic ants, bee-parasitic beetles and ant-parasitic Lepidoptera [27][28][29]. Alternatively, P. grandior may maintain a weak mimicry to all present hosts and/or reduce the CHC profile complexity and/or CHC amounts (insignificance strategy).…”
Section: Introductionmentioning
confidence: 99%
“…(v) Do larval growth patterns vary between different regions? Although we and colleagues have demonstrated the existence of the growth polymorphism in M. rebeli larvae from the Gap region of the Hautes‐Alpes and the Rhône‐Alpes in France, the Spanish Pyrenees, and the Black Forest, Germany, it is apparently absent from north Italian (Casacci et al ., ) and Hungarian populations (A. Tartally, pers. commun.)…”
Section: Introductionmentioning
confidence: 99%